Strategi Smart Tourism Pemerintah D.I. Yogyakarta di Era New Normal - Rimapradesi, Yulia; Surwandono, (Sospol, 2022)
Crowd prevention imposed by the implementation health protocol of covid-19 caused decrasing tourism sector income, particularly in the province of D.I. Yogyakarta. Local government of Yogyakarta established SIWIGNYO as a program to revitalise tourism economic development in the new normal period. Based on qualitative research method, data obtained from literature reviews on research publication, government reports, and content analysis on digital information and social media contents, such as Youtube, as well as the online applications. It examines the optimalization of the Visiting Jogja and Jogja Pass created by the Department of Tourism in partnership with the Department of Communication and Information as online application to support Yogyakarta smart tourism destination. Visiting Jogja was developed to offer comprehensive details on tourist locations, weather predictions, and both cash and non-cash ticket reservations. The government can also get real-time statistics data to count tourism arrivals for each destination. Meanwhile, the Jogja Pass used to self-screening tool that determines visitor IDs, suggestions for medical services, and the management of crowd prevention. Promotion of tourist destinations by the DIY government utilizes Virtual Tour 360 through the youtube channel. The results of this study conclude that DIY tourism policy innovation provides systematic information, transaction certainty, and is easily accessible to the wider community, both visitors and economic actors.